2014
DOI: 10.4193/rhin12.198
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after endoscopic sinus surgery or balloon sinuplasty: a randomized clinical study

Abstract: Both balloon sinuplasty and endoscopic sinus surgery improved the quality of life of patients with mild chronic or recurrent rhinosinusitis. However, the remarkably higher material cost of balloon sinuplasty compared to ESS sets limits on its broad use. There is an obvious need for further study to find out if, as an office procedure, balloon sinuplasty could deliver cost-savings high enough to cover the higher material cost of balloon sinuplasty. Our study was, however, too small to enable firm conclusions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 6 publications
1
41
1
Order By: Relevance
“…This trial differed from the present series in that both arms were treated under general anesthesia. Similar findings were also reported by another group who employed SNOT‐22 scoring to examine outcomes at 3 months in 30 patients randomized to either balloon sinus dilation or FESS . Although these smaller randomized trials did not achieve the enrollment necessary to provide statistical power (0.8), it is noteworthy that their observations are indeed consistent with those of the REMODEL trial, which demonstrates persistent benefit up to 2 years after treatment across an array of both rhinologic and nonrhinologic symptoms.…”
Section: Discussionsupporting
confidence: 78%
“…This trial differed from the present series in that both arms were treated under general anesthesia. Similar findings were also reported by another group who employed SNOT‐22 scoring to examine outcomes at 3 months in 30 patients randomized to either balloon sinus dilation or FESS . Although these smaller randomized trials did not achieve the enrollment necessary to provide statistical power (0.8), it is noteworthy that their observations are indeed consistent with those of the REMODEL trial, which demonstrates persistent benefit up to 2 years after treatment across an array of both rhinologic and nonrhinologic symptoms.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, patients with a prolonged and chronic disease with a severe impact on quality-of-life might benefit more from surgery than continued medical therapy [5]. Controlled studies have shown quality-of-life (QoL) improvement after ESS and balloon sinuplasty [2,6,7]. Balloon sinuplasty has been under an intensive evaluation during the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantages of the procedure are the lack of knowledge of its long-term effect, the high costs of the disposable instruments, and its technical limitations in ethmoidal area or in removal of atypical mucosa [9]. Several uncontrolled and controlled studies have suggested balloon sinuplasty to be a safe and effective method [6,7,[10][11][12][13]. However, the limitations of these studies are the heterogeneity of patients and procedures as well as short follow-up time, which makes the conclusions difficult to draw.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cone beam computed tomography scans of the paranasal sinuses were performed to evaluate the status of the paranasal sinuses . Patients were allocated into two groups, mild changes (score per side 1–2) or severe changes (score per side 3–4), based on the Lund‐McKay score …”
Section: Methodsmentioning
confidence: 99%